A review of washback and its pedagogical implications - Pan, Yi-Ching (VNU Journal of Foreign Studies, 2009)
Abstract. The way in which examinations influence teaching and learning is commonly described as “washback” or “backwash”. A number of definitions have been proposed for the term “washback” throughout the published research and literature on language testing. This study starts with a focus on the various definitions of backwash or washback. Next, it examines the similar concept terms defined by other researchers. By reviewing the variety of definitions, the researcher’s own view of washback will be reached. Comes after that are the explorations of different types of washback. The studies ends with drawing pedagogical implications for EFL teachers.